Security analysis of cloud services - Maskaliunets, Stanislau; Novotný, Ota, 1971-; Šimeček, Karel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This thesis focuses on the issue of cloud service security. Its main goal is to familiarize readers with information security, with a special emphasis on information protection and threats in the field of information security. The work also includes an analysis of information security management and its implementation. The concept of cloud computing is analyzed in detail in the work, including the basic characteristics of clouds, distribution models and deployment models. Furthermore, the economic benefits of using cloud services are also discussed. On the basis of theoretical knowledge, a security analysis of the most popular cloud solutions was carried out. The work also includes an analysis of the cloud solution used by the University of Economics in Prague for generating Power BI reports. It is important to note that this thesis does not offer a single correct procedure in analyzing the security of cloud services. Rather, its goal is to introduce readers to the advantages and disadvantages of using cloud services in both work and personal life and to offer space for reflection on this topic.
Vedoucí práce: Ota Novotný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses